Pancreatic neuroendocrine tumor featuring growth into the main pancreatic duct and tumor thrombus within the splenic vein: a case report. Issue 7 (14th July 2020) - Miyata, Takashi; Takamura, Hiroyuki; Kin, Ryosuke; Nishiki, Hisashi; Hashimoto, Akifumi; Fujii, Yoritaka; Miura, Seiko; Fujita, Jun; Kaida, Daisuke; Tomita, Yasuto; Nakamura, Naohiko; Fujita, Hideto; et al.
Abstract: A 48-year-old woman was admitted to our hospital because of upper abdominal pain. Computer tomography showed an enhancing mass in the pancreatic body, dilation of the main pancreatic duct (MPD) and a filling defect within the splenic vein. On the basis of the preoperative diagnosis of pancreatic body cancer, distal pancreatectomy was scheduled. The pancreas was divided along the left edge of the gastroduodenal artery; however, frozen pathological examination of the pancreatic stump was tumor positive, and therefore a total pancreatectomy was performed. The lesion was a white expansive nodular mass that had spread into the MPD and protruded into the splenic vein. A pathological diagnosis of non-functioning neuroendocrine tumor (NET) was made. In general, imaging findings of disruption of the MPD and tumor vein thrombus are characteristics of pancreatic ductal adenocarcinoma, but are uncommon in NET. However, NET should be included in the differential diagnosis for such patients.